Adaptation to the Climate Change Impact through Community Participation on Customary Land Use - Zaflis Zaim; Imam Buchori (UIR PRESS, 2019)
Climate Change and global warming have brought some policy to reduce the impacts by adaptation and mitigation strategies. One adaptation strategy is to increase land use size in agriculture area base on community participation. On the other hand, sustainable development needs cooperation mainly on common investment. The aim of the study is to identify the land utilization process, role model and level of participation on customary land. We use observation and deep interview method to analyze this study. The result shows that the customary land utilization process has realized through public deliberation with local Fig.s. The agriculture programs operated with Wanatani concept or agro-forestry by housewives where multi-level strategy is mutually beneficial. Around 30 housewives have been participating in producing agriculture products, i.e., coffee, milk candy, palm sugar, and ginger powder. The level of participation especially for female farmers at RW 01, which shows a percentage of 16.6%. Generally, community participation has encouraged the gotong-royong model while has to contribute in their time, tools and materials to develop the communal shed. In conclusion, the land tenure system has taken with sharing benefits between local government & farmers. The customary tenure has recognized as one of the tenure systems in Indonesia, especially on Adat land management.